(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aimed to explore the viability of nitrogen distribution in milk to detect adulteration in market milk. Materials and Methods: Raw cow milk was obtained from the dairy farm at Bangladesh Agricultural University Dairy Farm (BAUDF). Fluid market milk, nonbranded bulk powdered milk, and local brand powdered milk were bought from the Mymensingh city area. The milk samples were T1 (milk from a known source—BAUDF, control group), T2 (reconstituted nonbranded bulk powdered milk), T3 (reconstituted local brand powdered milk), T4 (fluid market milk from Goala), T5 (mixture of 75% T1 and 25% T2), and T6 (mixture of 50% T1 and 50% T2). There were four replications in each variable, and the samples were tested for their physicochemical properties (specific gravity and acidity), gross composition (total solids, ash, milk fat, lactose, and total protein), and nitrogen distribution [casein nitrogen, noncasein nitrogen (NCN), and nonprotein nitrogen (NPN)]. Results: Statistical analysis revealed a significant difference (p < 0.05) among the milk samples about their physicochemical properties and gross composition. The T2 and T6 samples imparted lower protein content (p < 0.05). Much lower (p < 0.05) casein content was found in T2 and T6 than in T1. The NCN content among the samples also differed significantly (p < 0.05). All groups showed similar NPN values (p > 0.05) but the T1 (p < 0.05). Conclusion: The results from this study show the potential of the nitrogen distribution of milk to detect adulterated and reconstituted market milk; however, a hefty dataset is required before being adopted at the field level. J. Adv. Vet. Anim. Res., 11(4): 1023-1029, December 2024 http://doi.org/10.5455/javar.2024.k853